2017
DOI: 10.1111/1365-2656.12617
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic vs. static social networks in models of parasite transmission: predicting Cryptosporidium spread in wild lemurs

Abstract: Summary1. Social networks provide an established tool to implement heterogeneous contact structures in epidemiological models. Dynamic temporal changes in contact structure and ranging behaviour of wildlife may impact disease dynamics. A consensus has yet to emerge, however, concerning the conditions in which network dynamics impact model outcomes, as compared to static approximations that average contact rates over longer time periods. Furthermore, as many pathogens can be transmitted both environmentally and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…Universally, differences between types of covariation were strongest for theoretical pathogens with lower transmission efficiency, which suggests that such heterogeneity may be most important for less infectious, more chronic diseases in wildlife such as bovine tuberculosis (Cosgrove et al 2012). This finding is consistent with studies using empirically informed networks that have found dynamic interactions to be more important at lower transmissibility (Chen et al 2014, Springer et al 2017. Additionally, differences in the time it took to reach maximum prevalence for different types of covariation were most pronounced for simulations with higher variation in contact rate.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Universally, differences between types of covariation were strongest for theoretical pathogens with lower transmission efficiency, which suggests that such heterogeneity may be most important for less infectious, more chronic diseases in wildlife such as bovine tuberculosis (Cosgrove et al 2012). This finding is consistent with studies using empirically informed networks that have found dynamic interactions to be more important at lower transmissibility (Chen et al 2014, Springer et al 2017. Additionally, differences in the time it took to reach maximum prevalence for different types of covariation were most pronounced for simulations with higher variation in contact rate.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, incorporating dynamic, empirically-based interactions in livestock networks markedly changed predicted epidemic outcomes; Chen et al (2014) incorporated temporal variability with and without changes in individuals' degree order and observed greater discrepancies in predictions for pathogens with lower values of R 0 . Springer et al (2017) found that incorporating dynamic interactions increased the theoretical transmission of cryptosporidium through wild lemur networks. However, StehlĂ© et al (2011) suggested that daily aggregated networks were acceptable proxies for realtime dynamic networks for an SEIR model of conference attendees.…”
Section: Introductionmentioning
confidence: 99%
“…Social networks are increasingly integrating disease dynamics in their analyses (e.g. Springer, Kappeler, & Nunn, ; Vazquez‐Prokopec et al., ; Volz & Meyers, ) but to our knowledge no network‐based study has ever considered dynamic processes in both the pathogen and the host. The main challenge of social network analyses most likely lies in the difficulty of describing feedback dynamics between host social networks and disease‐related fitness costs in the host (Van Segbroeck, Santos, & Pacheco, ; Volz & Meyers, ).…”
Section: Discussionmentioning
confidence: 99%
“…A static network would thus overestimate the potential reach of the outbreak. Overall, Springer, Kappeler & Nunn () found largely overlapping estimates when comparing simulated spreads on dynamic and static representation of the same observation data: networks constructed from a population containing multiple groups of Verreaux's sifakas ( Propithecus verreauxi ). However, there was a general trend for larger outbreak sizes in static representations of the network, in line with expectations.…”
mentioning
confidence: 99%
“…Whether and how these factors are accounted for can fundamentally change the predicted impact of a spreading epidemic. Springer, Kappeler & Nunn (2017) investigate the role of different modes of transmission and network dynamics on the predicted size of a disease outbreak across several groups of Verreaux's sifakas, a group-living species of lemur. While some factors, such as seasonality, led to consistent differences in the structure of social networks, using dynamic vs. static representations of networks generated differences in the predicted outbreak size of an emergent disease.…”
mentioning
confidence: 99%